On the off-design of a natural gas-fired combined cycle with CO2 capture - Fredriksson Möller, Björn; Genrup, Magnus; Assadi, Mohsen (18th International Conference on Efficiency, Cost, Optimization, Simulation and Environmental Impact of Energy Systems (ECOS 2005), Trondheim, Norway, 2005-06-20 - 2005-06-22, 2005)
During the last 15 years cycles with CO2 capture have been in focus, due to the growing concern over our climate. Often a natural-gas fired combined cycle with a chemical absorption plant for CO2 capture from the flue gases have been used as a reference in comparisons between cycles. The integration of the steam production in the cycle to minimise the drop in efficiency have not been extensively studied. Neither have there been any studies on the off-design behaviour of such a plant if it should be built. In this paper the integration of steam production for regeneration of the amines is modelled at design load and studied in off-design conditions for a combined cycle. Different ambient conditions and part-load strategies and their influence on the cycle performance are also examined. Of particular interest is a novel strategy with the possibility of longer life of gas turbine blading, with marginal loss in efficiency. The off-design performance of the combined cycle is modelled in a rigorous way, using a gas turbine performance deck to calculate the performance of the gas turbine. The boiler is calculated using simplified correlations for off-design heat transfer and pressure drop. The steam turbine calculation is based on verified models for the flow - pressure - efficiency relations, whilst the steam condenser is based on the HEI (Heat Exchange Institute) method.
Keywords: CO2 capture; combined cycles; off-design